Akbar and the crows and other stories - "Horsburgh, Nicholas" (Karachi; Oxford University Press, 2013)
"Akbar and the Crows" is a popular folktale featuring Emperor Akbar and his witty advisor, Birbal. The story highlights Birbal's intelligence and quick thinking when Akbar asks an unusual question$1 (Bhow many crows are there in the city? Birbal cleverly responds with a humorous yet logical answer, stating that the number of crows equals the city's population and will change as birds come and go. The tale emphasizes wisdom, problem-solving, and humor, which are recurring themes in Akbar-Birbal stories.s
Keywords: folktales